2005
DOI: 10.1016/j.otohns.2005.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Benefits Resulting from 1‐and 6‐Hour Parathyroid Hormone and Calcium Levels After Thyroidectomy

Abstract: The new algorithm resulting from PTH and corrected calcium monitoring at 1 and 6 hours post-thyroidectomy has led to significant cost savings for our institution. It has also translated into greater patient satisfaction as a result of fewer blood tests, a lower incidence of transient hypocalcemia, and significantly shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 11 publications
0
77
0
9
Order By: Relevance
“…Almost all studies define hypocalcemia as either low serum calcium or development of symptoms of hypocalcemia (9,11,(15)(16)(17)(18)(19)(21)(22)(23)(24)(25)(26). We used only the symptoms of hypocalcemia because we believe that mixing two parameters (biochemical hypocalcemia and symptomatic hypocalcemia) can introduce a bias.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies define hypocalcemia as either low serum calcium or development of symptoms of hypocalcemia (9,11,(15)(16)(17)(18)(19)(21)(22)(23)(24)(25)(26). We used only the symptoms of hypocalcemia because we believe that mixing two parameters (biochemical hypocalcemia and symptomatic hypocalcemia) can introduce a bias.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors (3)(4)(5)(6) consider early postoperative (24-hour) serum calcium levels and intraoperative identification of parathyroid glands to be important predictive factors. Others (7)(8)(9) have instead suggested combining intact parathyroid hormone (PTH) and serum calcium measurements, arguing that PTH and serum calcium monitoring after the first postoperative hour would allow reliable prediction of postoperative hypocalcemia. Some authors (10)(11)(12) recommend quick PTH assay as a means of predicting postoperative parathyroid function, although others (13) found no overall significant difference in the capacity of intraoperative PTH levels, versus early postoperative serum calcium levels (day 1), to predict long-term hypoparathyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Early identification of patients at risk of hypocalcemia would allow prophylactic calcium supplementation therapy preventing development of symptomatic hypocalcemia. 6 In this study, 12 subjects had <12ng/ml parathyroid levels at 1,4,12 and 24 hours who were at high risk of developing hypocalcemia; started on oral calcium supplementation but later 2 (4%) out of 12 subjects developed symptoimatic hypocalcemia and 38 subjects had >/=12ng/ml parathyroid levels done at similar intervals as above were at low risk of developing hypocalcemia; although later 1 (2%) subjects developed symptomatic hypocalcemia as compared to study done by Chow et al, which used serum parathyroid levels as a criteria showed 2.8% of the patients developed hypocalcemia postoperatively. 7 Pattou et al, found that a postoperative PTH level of 12 pg/mL or less was a good predictor of hypocalcemia, but they did not state how long after surgery PTH values were obtained.…”
Section: Discussionmentioning
confidence: 99%